Characterizing the Folding Transition-State Ensembles in the Energy Landscape of an RNA Tetraloop - Viegas, Rafael G. [UNESP]; Sanches, Murilo N. [UNESP]; Chen, Alan A.; Paulovich, Fernando V.; Garcia, Angel E.; Leite, Vitor B. P. [UNESP] (American Chemical Society (ACS), 2023)
Molecular dynamics (MD) simulations have become increasingly powerful and can now describe the folding/unfolding of small biomolecules in atomic detail. However, a major challenge in MD simulations is to represent the complex energy landscape of biomolecules using a small number of reaction coordinates. In this study, we investigate the folding pathways of an RNA tetraloop, gcGCAAgc, using five classical MD simulations with a combined simulation time of approximately 120 μs. Our approach involves analyzing the tetraloop dynamics, including the folding transition state ensembles, using the energy landscape visualization method (ELViM). The ELViM is an approach that uses internal distances to compare any two conformations, allowing for a detailed description of the folding process without requiring root mean square alignment of structures. This method has previously been applied to describe the energy landscape of disordered β-amyloid peptides and other proteins. The ELViM results in a non-linear projection of the multidimensional space, providing a comprehensive representation of the tetraloop’s energy landscape. Our results reveal four distinct transition-state regions and establish the paths that lead to the folded tetraloop structure. This detailed analysis of the tetraloop’s folding process has important implications for understanding RNA folding, and the ELViM approach can be used to study other biomolecules.